Correlation Between Total Iron Intake And Folic Acid On Hemoglobin (Hb) Levels Of Adolescent Girls At Muhammadiyah 10 GKB Senior High School - Musammah, Anjali; Rahma, Amalia; Supriatiningrum, Dwi Novri (Universitas Muhammadiyah Gresik, 2023)
The purpose of this study was to analyze the relationship between total iron intake and folic acid to hemoglobin (Hb) levels of adolescent girls at Muhammadiyah 10 GKB Senior High School. This research method used quantitative research with an analytic observational approach. The population was 224 female students at Muhammadiyah 10 GKB Senior High School who were taken using purposive random sampling technique. Data were collected using FFQ questionnaire, 3x24 hour estimated food records questionnaire, food photo book, Digital Hemoglobinometer, and Hb level measurement result form. Data analysis used Pearson Correlation test. The results showed a significant relationship between iron intake (Sig = 0.042), folic acid (Sig = 0.035) with hemoglobin levels in adolescent girls at Muhammadiyah 10 GKB Senior High School. The conclusion in this study is that interventions need to be carried out including iron tablet supplementation, education, and efforts related to increasing iron and folic acid intake through food.